THE ROLE OF KEY FACTORS OF TRAINING TRANSFER ON EMPLOYEE'S JOB PERFORMANCE: A REVIEW - Bin Zahari, Ibrahim; Fayeq Obaid, Tareq (European Scientific Journal, ESJ, 2014)
One of the most critical challenges facing the developing countries is the training and development of its people, employees are the one the critical strategic asset in any organization. By improving their employee’s skills at work environment, organizations can act as successful and highly compete within the domain of their courses of action. Not all employees are same in their working capacities and they have different modes of behavior regardless of the rewards. In order to judge the work performance of employee, the most common management practices employed, all over the world, is performance assessment. This research aims at investigating the impact of training transfer on job performance and how they correlate with each other within the context of Higher Education organizations in Palestine. Employees only seem to use knowledge, skills and attitudes from corporate training programs to a very limited extent at their workplaces. It has often been argued that training factors has a significant role in improving the performance, and what is the role of training transfer on the relationship, unfortunately, within Palestinian context there are ambiguity in previous research, thus the study recommend for future research to investigate the relationship between pre-training factors, training transfer and performance in Palestine within educational context.